(untitled) (Eurasian Scientific Herald, 2023)
Linguistic competences of a foreign language teacher are new entities formed on the basis of psychology and pedagogy, which manifest various aspects of the cognitive behavior of the teacher’s preparation for the future activities as the integrative characteristics of the person.